Pet tolminskih književnikov med literarnozgodovinsko in šolsko kanonizacijo - Božič, Zoran (Slavistična revija, 2014)
The five Tolmin authors who were at the turn of the last decade the object of special attention due to the anniversaries of their births or deaths, have also been included in almost every Slovene literary history, although their compilers assigned them various canonical statuses. Even greater differences among them become evident in analyses of secondary school readers, which in selecting authors and their literary works employ reception-related criteria in addition to other literary-historical criteria. The highest canonical positions in Slovene literary history textbooks are occupied by Ivan Pregelj, France Bevk, and Ciril Kosmač. Saša Vuga has been gaining in significance in recent decades, while Ljubka Šorli remains a relatively marginal author. In Slovene secondary school readers, the test of time has been adding weight to the work of Ciril Kosmač, while on the other hand, France Bevk's literature has been losing importance since the independence of Slovenia and Saša Vuga has been entirely absent from secondary school readers because of the exceptionally complex reception of his literary work.
Keywords: Bevk, France, 1890-1970; history of literature; kanonizacija; Kosmač, Ciril, 1910-1980; literarna recepcija; literarna zgodovina; Pregelj, Ivan, 1883-1960; Slovene literature; slovenska književnost; srednješolska berila; Šorli, Ljubka, 1910-1993; Vuga, Saša, 1930-